Modul Penerimaan Diri dan Kebahagiaan Perempuan dalam Work Family Balance Pemberdayaan Masyarakat Madani - Rahmawati Rahmawati; Wika Hardika Legiani; Stevany Afrizal; Diah Utamy; Aenunnisa Aenunnisa (Jurnal Penelitian Bimbingan dan Konseling, 2019)
This study aims to design and test the feasibility the modul of self-acceptance  and women happiness in work-family balance, that used to minimize family conflict due to tension and stress in dealing with multiple roles (as laborers/workers and as wives/housewives). The approach used is research and development (Research and Development) by taking female respondents who have double duties as workers and housewives from the Kasemen Kelurahan, Serang City, Banten Province. Data collection uses a scale of feasibility measurement and professional judgment then analyzed using quantitative descriptive analysis techniques. The self-acceptance and happiness modules of women in work-family balance were developed in the form of a training module book. The results of this study are the book Module of self-acceptance and women's happiness in work-family balance. Based on the results of the feasibility test of the material and the learning modules tested to experts, the feasibility value of the module material was 88.15%, and the feasibility of the module delivery was 86.11%. While the feasibility value of practicing modules delivered by women module users was 82.66%. Based on these results it can be concluded that the learning modules developed according to material experts, instructional media experts, and potential female users are very feasible, and can be used to support the implementation of women self-acceptance and happiness training in the work-family balance of civil society empowerment. Keyword : learning modules, self-acceptance, happiness, work-family balance